2020
DOI: 10.1111/ijfs.14851
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and physiological changes during the ripening of Banana (Musaceae) fruit grown in Colombia

Abstract: The physicochemical and physiological attributes of three contrasting commercial varieties of Musaceae, Dominico Harton (plantain), Guineo (cooking banana) and Gros Michel (dessert banana), were evaluated and statistically analysed during post-harvest ripening. Quality attributes differed markedly among varieties, both in fresh fruits and during ripening. Variety (V) had a significant effect (P < 0.001) on all attributes except total soluble solids (TSS), carotenes and total chlorophyll. Storage time (ST) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
(49 reference statements)
3
11
0
2
Order By: Relevance
“…Experimental evidence from postharvest metabolism also supports the model: tomato fruits stored postharvest under low or chilling temperatures undergo bursts of stress-related carbon dioxide and ethylene production when allowed to recover at room temperature, with an accompanying and corresponding decrease in starch reserves [ 158 , 159 ]. A similar inverse relationship between starch content and respiratory activity was observed in ripening banana [ 96 , 160 162 ], ginger rhizomes [ 163 ] sunberry [ 164 ], apple [ 165 ] and durian [ 166 ] (Figure S6 ; Table S3 ). The relationship between tissue starch content and respiration may not be perfectly linear in all species, e.g., in stored ginger, starch showed a biphasic accumulation pattern as respiration progressed, a trend not seen in other tissues examined (Figure S6 ; Table S3 ).…”
Section: Putative Role Of Sbes As Determinants Of Postharvest Quality In Horticultural Cropssupporting
confidence: 67%
See 1 more Smart Citation
“…Experimental evidence from postharvest metabolism also supports the model: tomato fruits stored postharvest under low or chilling temperatures undergo bursts of stress-related carbon dioxide and ethylene production when allowed to recover at room temperature, with an accompanying and corresponding decrease in starch reserves [ 158 , 159 ]. A similar inverse relationship between starch content and respiratory activity was observed in ripening banana [ 96 , 160 162 ], ginger rhizomes [ 163 ] sunberry [ 164 ], apple [ 165 ] and durian [ 166 ] (Figure S6 ; Table S3 ). The relationship between tissue starch content and respiration may not be perfectly linear in all species, e.g., in stored ginger, starch showed a biphasic accumulation pattern as respiration progressed, a trend not seen in other tissues examined (Figure S6 ; Table S3 ).…”
Section: Putative Role Of Sbes As Determinants Of Postharvest Quality In Horticultural Cropssupporting
confidence: 67%
“…Starch, or the proportion of the amylose fraction of starch, is used as a common ripening biomarker for apple [ 94 ], banana [ 95 , 96 ], and pear [ 97 ]. This marker relies on the ability of amylose to physically interact with iodide to form a triiodide blue-black complex.…”
Section: Main Textmentioning
confidence: 99%
“…Furthermore, these findings are consistent with Maduwanthi and Marapana [50], who reported that the fresh pulp of the green fruit contains only approximately 1 to 2% sugar, which climbs to 15 to 20% when the fruit at ripeness. The respiration rate also increased from 6.7 to 77.084 (mL CO 2 /kg*hour) with increasing the ripening stage, and these findings are consistent with Moreno et al [4], who found that respiration rate continuously increased during storage for different banana varieties. Where at the start of storage, fruits were in a pre-climacteric stage, with a low baseline metabolism and respiration rate.…”
Section: Variation Of Biochemical Parameters Under Different Ripening...supporting
confidence: 90%
“…Fruit ripening is a genetically planned and highly coordinated process of organ transition from an unripe to a ripe state. As banana is a climactic fruit, during ripening, it undergoes a series of biochemical and physical changes that transform it into an edible fruit [3,4]. Several metabolic mechanisms are involved in these alterations, including starch to sugar conversion, color changes in the peel and pulp, cell wall degradation, and changes in volatile and acid concentrations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Acidity. An increase in respiration results in a corresponding increase in ripening leading to a sharp rise in TSS due to the breakdown of carbohydrates into sugar [47,68]. The reduction of TSS is associated with the utilization of sugars as carbon skeleton sources for the fungus [47].…”
Section: Total Soluble Solids and Titratablementioning
confidence: 99%